Pengaruh Tunneling Incentive, Bonus Mechanism, Debt Covenant dan Tax Minimization terhadap Keputusan Transfer Pricing - Amilia Riska; Saiful Anwar (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2021)
Transfer pricing practices can be caused by a special relationship where the company can take advantage of the opportunities that exist in the company. This study was used to examine the variables of tunneling incentive, bonus mechanism, debt covenant, and tax minimization on transfer pricing decisions. This research uses the help of WarpPLS 6.0 software. The technique used is purposive sampling by determining the various criteria needed. This study shows that tunneling incentives have an effect on transfer pricing with the implication that the greater the share ownership, the higher the level of the company in conducting tunneling activities to influence transfer pricing decisions. The bonus given to the manager can be seen from the quality of the manager's work so that the greater the bonus received, the higher the company's motivation to carry out transfer pricing activities. Meanwhile, debt covenants and tax minimization have no effect on transfer pricing decisions. The implication is explained that if the reported profit is higher, it will lead to technical negligence and become the cause of the company not being interested in carrying out transfer pricing practices.